2020
DOI: 10.17263/jlls.803828
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of smartphone addiction levels of Turkish pre-service teachers with regards to various variables

Abstract: This research aims to determine the smartphone addiction levels of Turkish pre-service teachers. In this study, a relational screening model, which is one of the quantitative research methods, was used. The study group consists of 178 pre-service teachers studying at a State University in the West of Turkey. Smartphone Addiction Scale adapted to Turkish by Demirci, Orhan, Demirdas, Akpınar and Sert (2014) were used in the research. Data analysis in the research was done through the SPSS 25 package program. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(8 reference statements)
1
2
0
1
Order By: Relevance
“…As the time spent by the students on smartphones increased, their smartphone addiction increased. Similar results have been reported in previous studies (Geçgel, 2020;Yaran, 2020). Tanhan (2020) in a quite new and innovative qualitative study called Online Photovoice (OPV) found that college students reporting technology addiction during the COVID-19 pandemic as one of the most important barriers to their mental health.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…As the time spent by the students on smartphones increased, their smartphone addiction increased. Similar results have been reported in previous studies (Geçgel, 2020;Yaran, 2020). Tanhan (2020) in a quite new and innovative qualitative study called Online Photovoice (OPV) found that college students reporting technology addiction during the COVID-19 pandemic as one of the most important barriers to their mental health.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…Benzer şekilde (Belli, 2018;Güngör ve Koçak, 2020) ergenlerin akıllı telefon bağımlılık düzeyleri ile akıllı telefon kullanım süreleri arasında pozitif ilişki bulgulamış ve akıllı telefon bağımlılığı puanları kullanım süresi 5 saat ve fazla olan ergenlerde daha yüksek bulgulanmıştır. Bağımlılık yapıcı ile uzun zaman harcanması bağımlılık oluşumuna sebebiyet verdiği düşünülürse literatürde benzer sonuçlara ulaşan çalışmalara rastlanması olağandır (Aljomaa vd., 2016;Dirik, 2016;Çakır ve Oğuz, 2017;Çetiner, 2020;Geçgel, 2020;Çiçek vd., 2021;Kapudere, 2020). Akıllı telefon kullanım süresi bağımlılık geliştirme üzerinde etkili bir faktördür (Akkaş, 2019).…”
Section: Discussionunclassified
“…The studies conducted in the literature show that pre-service teachers who read more books have lower technology addiction [ 37 ]. In addition, there are also results that as the rate of reading books by pre-service teachers decreases, their interest in technology increases and negatively affects health [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies conducted in the literature show that pre-service teachers who read more books have lower technology addiction [ 37 ]. In addition, there are also results that as the rate of reading books by pre-service teachers decreases, their interest in technology increases and negatively affects health [ 37 , 38 ]. In this context, teachers raising future generations should also have reading habits because a teacher should show exemplary role-model behaviors to their students.…”
Section: Introductionmentioning
confidence: 99%